A Study on Teachers’ and Students’ Speaking Anxiety: : The Causes and Strategies to Overcome It - Tedjasuksmana, Hendra; Listyani, Listyani (Universitas Dian Nuswantoro, 2024)
Anxiety about speaking English is not unusual and can affect any language learner, including teachers can experience anxiety in speaking English. When a person experiences this anxiety, they must have strategies to overcome it. While studies usually focus on students, this current study aims to explore teachers’ anxiety as well. This paper addresses three research questions: [1] What type of anxiety do the respondents experience? [2] What causes them to suffer from speaking anxiety? and [3] What strategies do they use to overcome their anxiety? Data in the form of responses from seventy-five respondents were gathered during a workshop conducted by a postgraduate program of a private university in Surabaya, East Java. The respondents were asked about their worries, causes, and strategies to overcome their anxiety. The problems were categorized into psychological, social, and language proficiency. The findings revealed that the respondents experienced social, psychological, and language-proficiency issues. Besides that, the respondents had their strategies for overcoming their anxiety. Only 14 respondents out of 75 mentioned the strategy they had to overcome their speaking anxiety. The results of this research can help university lecturers boost their students’ confidence and motivation in speaking enabling them to become competent English teachers.